A Person-Centered Approach to Prison Behavior Based on Officers’ Observations: Relations to Risk, Prison Misconduct, and Recidivism - Hausam, Joscha; Lehmann, Robert J. B.; Dahle, Klaus-Peter (Frontiers in Psychiatry, 2020)
Incorporating measures of prison behavior into risk assessment and management proce-dures may assist in treatment planning, risk monitoring, and decision-making. A behavior rating scale was used to assess prison officers’ observations on externalizing, internalizing, and adaptive behavior in a sample of 277 sexual and violent offenders in correctional treat-ment in Berlin, Germany. The present study employed latent profile analysis to identify in-mate subtypes with similar behavioral patterns. Results indicated a solution with five latent profiles that showed similarities with previous inmate typologies. The subtypes were termed “Aggressive-Psychopathic”, “Asocial”, “Situational”, “Inconspicuous”, and “Inadequate-Dependent”. Analyses attested to the construct and predictive validity of the subtypes and involved the examination of differences on criminological characteristics, risk assessment instruments, various types of prison misconduct and post-release recidivism. This person-centered study illustrates the importance of attending to broader patterns of inmate behav-ior. The structured assessment of behavioral observations by prison officers can be a valua-ble and easy-to-implement approach to benefit from this largely neglected resource.